2020
DOI: 10.1126/science.aba6652
|View full text |Cite
|
Sign up to set email alerts
|

SOSTDC1-producing follicular helper T cells promote regulatory follicular T cell differentiation

Abstract: Germinal center (GC) responses potentiate the generation of follicular regulatory T (TFR) cells. However, the molecular cues driving TFR cell formation remain unknown. Here, we show that sclerostin domain-containing protein 1 (SOSTDC1), secreted by a subpopulation of follicular helper T (TFH) cells and T–B cell border–enriched fibroblastic reticular cells, is developmentally required for TFR cell generation. Fate tracking and transcriptome assessment in reporter mice establishes SOSTDC1-expressing TFH cells as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 35 publications
2
28
0
Order By: Relevance
“…Sostdc1 plays many roles in development of tissues (including development of the eye [49]) and in promoting cancer. Recent study using SOSTDC1-reporter mice identified a potential regulatory role for Tfh-secreted SOSTDC1 in promoting the development of regulatory follicular T cells in germinal centers following viral infection or immunization [50]. Notably, these SOSTDC1-secreting Tfh cells expressed lower levels of Il21 and lost the ability to help B cells.…”
Section: Discussionmentioning
confidence: 99%
“…Sostdc1 plays many roles in development of tissues (including development of the eye [49]) and in promoting cancer. Recent study using SOSTDC1-reporter mice identified a potential regulatory role for Tfh-secreted SOSTDC1 in promoting the development of regulatory follicular T cells in germinal centers following viral infection or immunization [50]. Notably, these SOSTDC1-secreting Tfh cells expressed lower levels of Il21 and lost the ability to help B cells.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor necrosis factor receptor-associated factor 3 signaling maintains a high ICOS expression in Treg cells, and a high ICOS level is required for Tfr cell generation [64]. Moreover, in mice, sclerostin domaincontaining protein 1, secreted by a Tfh cell subpopulation, facilitates Tfr cell differentiation by blocking the Wnt/β-catenin axis, upregulating Foxp3, CXCR5, and CTLA-4 expression [65] (Fig. 2).…”
Section: Transcription Factorsmentioning
confidence: 99%
“…Recent evidence indicates that Tfh cells can convert into Tfr cells in an IL-2 dependent manner, providing new insights into regulation of Tfr/ Tfh balance (107). Moreover, in a breakthrough discovery, Wu et al (108) found a distinct subset of Tfh cells that could promote Tfr cell differentiation by blocking the Wnt-b-catenin axis in a sclerostin domain-containing protein 1-dependent (SOSTDC-1) manner. Elucidating the cellular and molecular mechanisms underlying the activities of Tfh and Tfr cells in the GC response as well as predominant determinants of the Tfr/Tfh balance will contribute to the regulation of autoantibody production.…”
Section: Involvement Of Tfh and Tfr In Autoimmune Diseases Tfh And Tfr Control Autoantibody Productionmentioning
confidence: 99%